Assessment of knowledge, attitudes, and willingness of pre-clinical nursing students to provide nursing care for people living with HIV/AIDS - Chanvatanak, Ly; Somnang, Phai; Rosa, Yi; Marong, Sann; Oun, Long Saw; Chourin, Tha; Soonbok, Park; Kieng, Sreyly (The Journal of Palembang Nursing Studies, 2022)
Background: HIV/AIDS as a global pandemic forced the nursing student to have appropriate knowledge and attitudes toward caring for people living with HIV/AIDS (PLWHA). Purpose: This study aims to explore the level of knowledge, attitudes, and willingness of pre-clinical nursing students to provide nursing care for PLWHA. Methods: A descriptive and cross-sectional study is conducted. A total of 185 pre-clinical nursing students enrolled in Bachelor of Science in Nursing (BSN), and Associate Degree in Nursing (ADN) programs were recruited. Data was collected from April to May 2019 using a self-reported questionnaire and analysed with descriptive statistics, a t-test, and Pearson’s correlation test with a significant level of 0.05. Results: Overall pre-clinical nursing students had moderate knowledge about HIV/AIDS, but students had a negative attitude toward HIV/AIDS. The students’ mean score of willingness to care for PLWHA was 5.45. BSN students had better knowledge than ADN students, and the difference was significant. However, differences in attitudes and willingness to manage between BSN and ADN students were insignificant. In addition, the differences in knowledge, attitudes, and desire to care between males and females were insignificant. The result revealed that attitudes and willingness to care for PLWHA were significantly correlated. Conclusions: Based on the study results, it is essential for nursing students to have accurate knowledge about HIV/AIDS and positive attitudes toward people with HIV/AIDS to ensure that they can provide high-quality and effective care for PLWHA as well as protect themselves from being infected with HIV.